2018
DOI: 10.1186/s12909-018-1320-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital storytelling in health professions education: a systematic review

Abstract: BackgroundDigital stories are short videos that combine stand-alone and first-person narratives with multimedia. This systematic review examined the contexts and purposes for using digital storytelling in health professions education (HPE) as well as its impact on health professionals’ learning and behaviours.MethodsWe focused on the results of HPE studies gleaned from a larger systematic review that explored digital storytelling in healthcare and HPE. In December 2016, we searched MEDLINE, EMBASE, PsycINFO, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 42 publications
0
66
0
5
Order By: Relevance
“…A literature review examining the role of emotion in learning and transfer of clinical skills found ‘emotion influences how individuals identify and perceive information, how they interpret it, and how they act on the information’ [ 16 ]. Similarly, a review of digital story-telling in healthcare details examples where digital stories engender empathy to a particular subgroup and alter attitudes and behaviours [ 9 ]. The authors of this review describe examples of co-creation of stories between healthcare professionals and patients, [ 9 ] and particularly in the setting of patient safety, the inclusion of patient voices may enrich narrative-based learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review examining the role of emotion in learning and transfer of clinical skills found ‘emotion influences how individuals identify and perceive information, how they interpret it, and how they act on the information’ [ 16 ]. Similarly, a review of digital story-telling in healthcare details examples where digital stories engender empathy to a particular subgroup and alter attitudes and behaviours [ 9 ]. The authors of this review describe examples of co-creation of stories between healthcare professionals and patients, [ 9 ] and particularly in the setting of patient safety, the inclusion of patient voices may enrich narrative-based learning.…”
Section: Discussionmentioning
confidence: 99%
“…One article describes how in a sample of 404 ‘college-age’ women, those exposed to expert-peer narrative videos about human papilloma virus vaccination were twice as likely to have sought out vaccination at 2 months compared with controls [ 8 ]. Its application in healthcare education has also been documented; a systematic review of digital storytelling for healthcare professions finds an ‘eclectic’ range of purposes for this approach, with the majority of studies identified applied in a nursing context [ 9 ]. This review found evidence of self-reported learning and behaviour change but highlighted the need for further research in the use and impact of digital storytelling in healthcare education and noted a minority of studies explored this approach in medical cohorts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 Storytelling is a description of an event that creates a memory in the student's mind. 19 According to The National Storytelling Network (www.storynet.org), "an effort to communicate events using words, pictures and sound". 18 Although nurses have always listened to patients' stories, storytelling has only been recognized as a teaching-learning strategy in nursing in the last decade.…”
Section: Storytellingmentioning
confidence: 99%
“…Storytelling can be used as a single strategy or combined with other strategies. [19][20] It has been described in studies that the use of storytelling can facilitate the association between theory and practice. The predominant benefit of using it as a teaching-learning strategy is that it promotes engagement beyond the classroom, as it makes content more interesting and memorable, acting as a trigger for information recall.…”
Section: Storytellingmentioning
confidence: 99%
“…Thus, we can admit that faculty members create this knowledge [9] and use it in the process of teaching students. Faculty members can share their knowledge with their peers to pave the ground for professional development and thus provide a platform for promoting pedagogical knowledge [6,10]. Hence, it is imperative that this knowledge be managed [11].…”
mentioning
confidence: 99%